2021
DOI: 10.2152/jmi.68.48
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off values for skeletal muscle strength and physical functions in Japanese elderly with walking difficulty

Abstract: Age-related changes in muscle strength and physical functions, and the association between vitamin D status and skeletal muscle functions were investigated in 36 men (21-90 years old) and 52 women (21-104 years old). Significant ageing-related decreases in several skeletal muscle functions and serum 25-hydroxyvitamin D [25(OH)D] levels were observed in both men and women. Cut-off values for the Timed up and go (TUG) test, walking speed, handgrip strength and Barthel Index (BI) detecting walking difficulties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The rate of aging processes is characterized by multifactorial variation. The older people get, the more they differ from each other in their morphofunctional characteristics ( 20 ). In old age, the supply of energy substrates to muscle fibers is impaired due to a sparse capillary network ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of aging processes is characterized by multifactorial variation. The older people get, the more they differ from each other in their morphofunctional characteristics ( 20 ). In old age, the supply of energy substrates to muscle fibers is impaired due to a sparse capillary network ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Involutionary processes affect on the impairment of the functions of the motor and postural system, on which postural stability depends. Postural stability is understood as the resistance of the posture to endogenous and exogenous disturbances, the source of which can be both environmental variability and the interaction of the organism with the environment ( 20 ). Changes in gait pattern (unsteady, small step without detaching the sole from the ground), cardiovascular and respiratory conditions, labile compensatory mechanism during locomotion in the environment are further risk factors for falls ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-lived individuals are more likely to have reduced handgrip strength (HGS). This reduction, associated with impaired cognitive function, can predict functional limitation 8,9 a higher risk of falls 10 and walking difficulties 11 in older adults. Recent studies demonstrated that the oldest old exhibit marked declines in neuromuscular abilities (strength, power, and endurance) that result in muscle atrophy and sarcopenia.…”
Section: -7mentioning
confidence: 99%